2016
DOI: 10.3390/ijerph13100963
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends in Geographical Variation in Breast Cancer Mortality in China, 1973–2005: An Analysis of Nationwide Surveys on Cause of Death

Abstract: To describe geographical variation in breast cancer mortality over time, we analysed breast cancer mortality data from three retrospective national surveys on causes of death in recent decades in China. We first calculated the age-standardized mortality rate (ASMR) for each of the 31 provinces in mainland China stratified by survey period (1973–1975, 1990–1992 and 2004–2005). To test whether the geographical variation in breast cancer mortality changed over time, we then estimated the rate ratio (RR) for the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 28 publications
1
17
0
3
Order By: Relevance
“…Some previous studies have reported a positive correlation between the socioeconomic level and breast cancer mortality 34, 35 . In Shandong, the economy in the eastern region is more developed compared to the central and western regions.…”
Section: Discussionmentioning
confidence: 91%
“…Some previous studies have reported a positive correlation between the socioeconomic level and breast cancer mortality 34, 35 . In Shandong, the economy in the eastern region is more developed compared to the central and western regions.…”
Section: Discussionmentioning
confidence: 91%
“…Inicialmente são consideradas pesquisas que utilizaram somente o mapeamento geográfico para analisar a distribuição da incidência e mortalidade por câncer de mama, destacando-se em termos internacionais: Fukuda et al (2005), Vieira et al (2008), Alvarez et al (2009) Xia et al (2016). Já em nível nacional, tem-se: Wünsch Filho & Moncau (2002), Santos et al (2009) e Zapponi & Melo (2010).…”
Section: Revisão De Literaturaunclassified
“…Já Xia et al (2016) avaliaram dados de mortalidade por câncer de mama em 31 províncias da China em três diferentes períodos: de 1973 a 1975, 1990 a 1992 e 2004 a 2005. Baixas taxas de mortalidade pela doença foram observadas na China Ocidental (Noroeste e Sudoeste), enquanto altas taxas foram encontradas no Nordeste da China.…”
Section: Revisão De Literaturaunclassified
See 1 more Smart Citation
“…A set of diagnosis methods for breast cancer have been studied by experts, looking for early detection, finding that the primary method—breast self-examination—is not adequate, since there is no evidence of a reduction in the mortality rate due to this disease in women who practice breast self-examination against to those who do not [8,9,10]. …”
Section: Introductionmentioning
confidence: 99%